ASSISTANCE IN INVOICE DATA COLLECTION PT. GAPURA ANGKASA FOR THE EFFICIENCY OF FINANCIAL MANAGEMENT - Putra, I Wayan Eka; Dianti, Indah; Anggreni, Luh Jaya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Procurement of goods must have a good financial system to support all activities carried out by the company. The developed financial system must also have controls aimed at managing incoming goods, used goods, stock, transaction processing results, and transaction results reports. The purpose of this service activity is to assist in collecting invoice data in support of the efficiency of the financial management system used at PT. Gapura Angkasa. So it is necessary to use a web-based information system so that the transactions carried out can be well organized and clear. PT. Gapura Angkasa Denpasar Branch in collaboration with PT. Garuda Indonesia and PT. Angkasa Pura which is engaged in the field of ground handling services and other business activities that support the aviation business at airports. At first the procurement of goods in and out at PT. Gapura Angkasa is still manual, so a web-based information system is needed that can simplify and speed up service. This system can only be accessed by employees or officers at PT. Gapura Angkasa. To design this procurement system, structural design is used, namely by using an Enttity Relationship Diagram (ERD), making Data Flow Diagrams (DFD), making billing and recording transactions using Data Invoices EXCEL, and MySQL as data storage databases.